Proboitics and their Role in GI Diseases (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Objective: To evaluate role of probiotics in human physiology, metabolism, health, immunity and GI disorders.It is important for gastroenterologists to improve their understanding of the mechanisms of probiotics and the evidence that support their use in clinical practice.Data Sources: A medline search (1948-December 2014) was conducted using GI diseases and probiotics as terms for identifying pertinent studies. Search limits included English language. Additional information was obtained from bibliographies.Data Selection And Data Extraction: The information provided is based on review of primary literature from randomized controlled trials (RCTs), meta-analyses, expert consensus panel recommendations and society-based practice recommendations. References are provided for more reading and figure summarizes key information about their mechanism of action.Data Synthesis: The need for objective, evidence-based guidance on the role of probiotics is becoming increasingly important as public awareness grows. This consensus is intended as a practical reference to help physicians make appropriate, evidence-based recommendations to patients who might benefit from probiotic treatment. Overall, the randomised, placebo-controlled trials included in this article support, with a high evidence level, the therapeutic effects of probiotic agents for several disorders including antibiotic or Clostridium difficile-associated diarrhea, irritable bowel syndrome, and the inflammatory bowel diseases. Although probiotic research is a rapidly evolving field, there are sufficient data to justify a trial of probiotics for treatment or prevention of some of these conditions. However, the capacity of probiotics to modify disease symptoms is likely to be modest and varies among probiotic strains and not all probiotics are right for all diseases. The goal of this review is to provide clinicians with an overview of the rationale and data which support or refute the role of probiotics for treating commonly encountered gastrointestinal disorders.J Bangladesh Coll Phys Surg 2016; 34(2): 92-99